The Social Motive Behind the Inclusion of Moses Story Within Andalusi Poetry - فاطمة حيدر علي رغد فاضل علي (College of Education for Women, 2019)
The significance of the social motivation lies in showing the great and important role of the story of the prophet of ( Moser ( Peace upon him) in Quran , especially , it is considered the greatest one in Quran , as that confirmed by the poets of Andalusera ,as it includes aspects similar to that prevailing over in their environments and their social life via the social motivation. Moreover , the relation's poets with the Andalus society where suitability prevailing over consistent with the events of the story; bedsides, artistic expression about the society for being considered as a trust mirror reflect real facts surrounded by the Andalussociety with all its sides and aspects . Thus , the poet takes Quran , especially the story of Moser for being consistent with the events of the Andalus society and that being considered as an example that should be followed up as to express negative and positive aspects of the society.